iFloW: an integrated logistics software system for inbound supply chain traceability - Santos, Nuno António Lira Fernandes Faria (2016)
Visibility plays an important role in supply chain management. Such visibility is not only important for better planning, but especially for real-time execution related with the traceability of goods. In inbound supply chain management, logistics planners need to trace raw materials from their requests in order to properly plan a plant’s production. The iFloW (Inbound Logistics Tracking System) integrates logistics providers IT applications and Global Positioning System (GPS) technology to track and trace incoming freights. The Estimated Time of Arrival (ETA) is updated in real-time allowing an improved materials planning process. This paper presents the iFloW project and describes how these issues are addressed and validated in a real pilot project.